2022
DOI: 10.1021/acsfoodscitech.1c00448
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Utilization of Pulse Protein in Food and Industrial Applications

Abstract: Innovations in the plant protein space have made significant strides in the past few years. A substantial body of work is to replace animal protein-based products with plant protein ingredients. Pulse proteins are receiving utmost attention among these plant proteins due to their nutritional and functional properties. This article critically evaluates the food and non-food applications of pulse protein and intends to present the most current knowledge with interest to stimulate further research to optimize pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 158 publications
(347 reference statements)
0
13
0
Order By: Relevance
“…45 It is also suggested that there is a need for thorough research due to their functional potential in the food industries, as well as their use in non-food industries. 46…”
Section: Need For Pulse-based Products and Their Importancementioning
confidence: 99%
“…45 It is also suggested that there is a need for thorough research due to their functional potential in the food industries, as well as their use in non-food industries. 46…”
Section: Need For Pulse-based Products and Their Importancementioning
confidence: 99%
“…The versatility of proteins is embedded in their amphipathic nature enabling them to act as a surface‐active agent for interaction with other food components and air (Akharume et al., 2021; O'Sullivan et al., 2016; Popkin et al., 2012). Regardless of the protein source, solubility, viscosity, foaming ability, emulsification capacity, gelation, water‐holding capacity (WHC), and oil‐holding capacity (OHC) are some of the most critical protein techno‐functional properties of utmost importance in the food industry (Bandara et al., 2018; Hadnađev et al., 2017; Nadeeshani et al., 2022). Additionally, the digestibility and bioaccessibility of dietary protein are other factors influencing protein application in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Among plant derived proteins, legume protein is of wide interest as a result of its low cost, high nutritional value and high bioavailability. 5,6 Mung bean (Vigna radiate. L) is a legume with a high protein content (14.6-32.6%).…”
Section: Introductionmentioning
confidence: 99%